2017
DOI: 10.1111/imj.13428
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori infection and vomiting induced by gastrointestinal cancer chemotherapy

Abstract: H. pylori infection in patients with cancer may be a factor that increases CINV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is so common that more than 50% of the global population harbors the bacterium. H. pylori modulates Wnt/β-catenin-mediated tumorigenesis in human gastric cancer, but the relationship between H. pylori and chemotherapy controversial [53,54]. In our study, we observed that H. pylori leads to the high antioxidant status of cancer cells by upregulating GPX4 expression and activity via TCF4.…”
Section: Discussionmentioning
confidence: 55%
“…It is so common that more than 50% of the global population harbors the bacterium. H. pylori modulates Wnt/β-catenin-mediated tumorigenesis in human gastric cancer, but the relationship between H. pylori and chemotherapy controversial [53,54]. In our study, we observed that H. pylori leads to the high antioxidant status of cancer cells by upregulating GPX4 expression and activity via TCF4.…”
Section: Discussionmentioning
confidence: 55%
“…This tool has been widely used in clinical practice. [31][32] The MAT is a reliable and valid clinical tool.…”
Section: Mascc Antiemetic Tool(mat)mentioning
confidence: 99%